Staff attitudes towards young people in looked after accommodation. Issue 4 (4th November 2014) - Copley, Jennifer; Johnson, Dan; Bain, Stella
Abstract : Purpose: – To consider the power of psychological well-being, empathy and coping style in predicting staff attitudes towards young people in looked after accommodation, involved in or at risk of offending behaviour. The purpose of this paper is to understand more about staff attitudes which have a significant role in the care and rehabilitation of this client group. Design/methodology/approach: – Psychological well-being, empathy and coping style are discussed in terms of their impact on attitudes towards young people. The predictive power of each factor is considered using multiple regression analysis of participants' responses on an adapted version of the Attitudes to Prisoners (ATP) scale, the General Health Questionnaire (GHQ), the Interpersonal Reactivity Index (IRI) and the Coping Styles Questionnaire (CSQ). Findings: – Multiple regression analyses showed that empathic concern (affective empathy) was the only factor predictive of attitudes towards young people. The paper discusses the applied implications for employers, including the possibility of empathy training for staff members and highlights the need for further consideration of the factors impacting on staff attitudes. Practical implications: – The outcome suggests that empathy may serve as a protective factor against the development of negative attitudes. This highlights the importance of fostering staff empathy and the possible use of empathy training. Originality/value: – The research findings question the robustness of the relationships between staff psychological well-being, empathy, coping styles and attitudes towards their client group. The outcome suggests that empathy may serve as a protective factor against the development of negative attitudes.